Image Steganography Using Hash Function And Compression - Ahmad Sulaiman, Zurkifli (2023)
An image steganography is a method for concealing any data or secret messages within an image file. In this study, image steganography, which uses a secret key to improve hidden information security while enhancing the LSB approach, is introduced. Before being embedded into a cover image, the message image will be compressed using lossy compression algorithms to reduce the size of the image. Prior to and following the embedding of a message image, the cover image is hashed using the hash function. The hash function will be used in the stego image, and the result will be kept in the host image for additional verification throughout the extraction process. The suggested technique uses hash function and lossless compression to illustrate image steganography.